Dysregulation in B‐cell responses and T follicular helper cell function in ADA2 deficiency patients. Issue 1 (28th August 2020) - Schena, Francesca; Penco, Federica; Volpi, Stefano; Pastorino, Claudia; Caorsi, Roberta; Kalli, Francesca; Fenoglio, Daniela; Salis, Annalisa; Bertoni, Arinna; Prigione, Ignazia; Bocca, Paola; Insalaco, Antonella; et al.
Abstract: Adenosine deaminase 2 deficiency (DADA2) is an autoinflammatory disease characterized by inflammatory vasculopathy, early strokes associated often with hypogammaglobulinemia. Pure red cell aplasia, thrombocytopenia, and neutropenia have been reported. The defect is due to biallelic loss of function of ADA2 gene, coding for a protein known to regulate the catabolism of extracellular adenosine. We therefore investigated immune phenotype and B‐ and T‐cell responses in 14 DADA2 patients to address if ADA2 mutation affects B‐ and T‐cell function. Here, we show a significant decrease in memory B cells, in particular class switch memory, and an expansion of CD21 low B cells in DADA2 patients. In vitro stimulated B lymphocytes were able to secrete nonfunctional ADA2 protein, suggesting a cell intrinsic defect resulting in an impairment of B‐cell proliferation and differentiation. Moreover, CD4 + and CD8 + T cells were diminished; however, the frequency of circulating T follicular helper cells was significantly increased but they had an impairment in IL‐21 production possibly contributing to an impaired B cell help. Our findings suggest that ADA2 mutation could lead to a B‐cell intrinsic defect but also to a defective Tfh cell function, which could contribute to the immunodeficient phenotype reported in DADA2 patients. Abstract : Mutations in ADA2 gene lead to a defective ADA2 enzymatic activity in B cells of patients, decreased production of inosine, and consequently an impaired B‐cell proliferation, differentiation to plasma cells (PC), generation of memory (Bm), and antibodies secretion. Also cTfh cells show a defect in IL‐21 production. This could explain hypogammaglobulinemia in this disease.